Conformation controlled stepwise hydride shuffling from the metal to the ligand backbone. Issue 21 (18th May 2020) - Wiedmaier, Nicholas R.; Speth, Hansjörg; Leistikow, Georg; Eichele, Klaus; Schubert, Hartmut; Mayer, Hermann A.; Wesemann, Lars
Abstract : The protonation of the benzo annulated cycloheptatriene PCP pincer ruthenium hydrido dicarbonyl complex using the superacid [H(Et2 O)2 ][BArF24 ] launches a cascade of hydride shifts which lead to the hydrogenation of the ligand backbone. Abstract : The benzo annulated cycloheptatriene PCP pincer ruthenium hydrido dicarbonyl complex syn -2 was prepared in one step by treatment of the ligand 1 with Ru3 (CO)12 . Protonation of syn -2 with the superacid [H(Et2 O)2 ][BArF24 ] [BArF24 ] − = tetrakis[bis(trifluoromethyl)phenyl]borate initiates the highly stereoselective hydrogenation of one of the double bonds in the cycloheptatriene backbone. This results in the formation of the pentacoordinate cationic 16-electron dicarbonyl ruthenium complex 3 . Hydrogenation of 3 with LiAlH4 generates the hydride complexes syn -4 and anti -4 which after protonation allow isolation of the symmetric 5 . In 5 a second double bond of the cycloheptatriene backbone was hydrogenated. Complex 5 was also obtained directly by the reaction of 3 with hydrogen (1 bar). Storage of 5 under a hydrogen atmosphere yields two pairs of η 2 -H2 complexes ( syn -7, anti -7 ) which are in a tautomeric equilibrium with their corresponding dihydrides ( syn -8, anti -8 ). A stepwise transfer of the hydrides to the ligand backbone can be deduced from the distribution of deuterium along the seven membered ring after applying the deuterated reagents (D +, D2 ). The observed stereochemistry suggests that the hydride transfer is controlled by conformational constraints.